(untitled) (Journal of Information and Communication Technology, 2023)
As Blockchain projects gain popularity among developers, the number of patched codes rapidly increases. With such growth, it is difficult for the few committers to maintain it in a timely manner. Subsequently, the community is always in search of new committers. This highlights the imperative importance of committer assessment decisions towards the success of Blockchain. However, the practices come with risks whereby new committers may harm the project. For example, a new committer may initiate a hard fork that splits a project. Numerous systematic literature reviews have investigated developer turnover’s impact on open-source software (OSS) projects. These studies mainly focused on aspects such as community participation, engagement, and motivation. However, previous reviews often overlooked committer assessment practices, particularly in the context of Blockchain projects. Although Blockchain operates as OSS, its distinct attributes, such as decentralisation and cryptography, justify the need for a dedicated review. Therefore, the objectives of this review are to 1) identify committer assessment practices, 2) identify problems in committer assessment, 3) identify existing factors in committer assessment, and 4) suggest some possible research topics. These goals were achieved through a systematic review of literature published between 2010 and 2022. The findings suggest that previous assessment models are useful but mainly focus on technical factors. The results also indicate that studies focusing on behavioural tendencies, which influence human activities, have so far been neglected. Finally, the paper concludes by charting potential open research opportunities.